A New Modification Method with Double Spline Curve for the Tooth Surface Design of Spur Gear - Wenjun Fan; Yuansheng Zhou; Xueqing Wang; Jinyuan Tang (Jixie chuandong)
A new tooth surface design is proposed to spur gears with a tooth surface modification defined by double spline curves， which are used to represent the tooth profile and longitudinal profile， respectively. The tooth surface is obtained by sweeping the tooth profile spline along the longitudinal profile spline. Compared to the traditional comprehensive modification， the tooth surface modification with double spline curves has more control variables， which makes the change of tooth surface geometry more flexible. Moreover， it can achieve the higher order continuity. Through the Finite Element Analysis （FEA）， the advantages of double spline curves modification are analyzed by comparing it with traditional comprehensive modification. The comparison indicates it has superior meshing performances， including the smooth curves of both transmission error and meshing stiffness and decreased frequency amplitudes of static transmission errors. The manufacturing feasibility of the proposed design is also validated by the real machining and measurement. The results show that the proposed new tooth surface modification method is an advanced and practical technology to design high performance spur gear.